2016
DOI: 10.1242/jcs.187815
|View full text |Cite
|
Sign up to set email alerts
|

Morphological process of podocyte development revealed by block-face scanning electron microscopy

Abstract: Podocytes present a unique 3D architecture specialized for glomerular filtration. However, several 3D morphological aspects on podocyte development remain partially understood because they are difficult to reveal using conventional scanning electron microscopy (SEM). Here, we adopted serial block-face SEM imaging, a powerful tool for analyzing the 3D cellular ultrastructure, to precisely reveal the morphological process of podocyte development, such as the formation of foot processes. Development of foot proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 42 publications
0
61
0
Order By: Relevance
“…Recently, Ichimura et al [2017] examined the morphological process of podocyte development in neonatal rat kidneys by block face SEM. The aim of their study was to determine the 3-dimensional morphological aspects of podocyte development, which are difficult to reveal using conventional SEM and TEM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ichimura et al [2017] examined the morphological process of podocyte development in neonatal rat kidneys by block face SEM. The aim of their study was to determine the 3-dimensional morphological aspects of podocyte development, which are difficult to reveal using conventional SEM and TEM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the EM techniques of serial block-face SEM (SBF-SEM) and focused ion beam SEM (FIB-SEM) have become available, both of which allow the 3D reconstruction of ultrastructural images with unprecedented speed and accuracy (Denk and Horstmann 2004; Heymann et al 2006). Excitingly, the application of the FIB-SEM technique has led to the discovery of so far unreported details during glomerular development (Ichimura et al 2017). Whereas, during the S-shape body stage, podocyte precursors have the known cobblestone appearance from the luminal side, their basolateral surface is irregularly shaped with the first cytoplasmic protrusions being inserted under neighboring podocytes.…”
Section: Structural Advancesmentioning
confidence: 99%
“…Meanwhile, ridge-like prominences develop at the base of primary foot processes, which find their way under neighboring podocytes, thereby separating their cell bodies from the GBM and creating the subpodocyte space. Once matured, primary processes form a cytoplasmic arcade that is often situated in the valleys between adjacent capillary loops (Ichimura et al 2017). …”
Section: Structural Advancesmentioning
confidence: 99%
“…6,11 Furthermore, reconstructed podocytes also clearly showed cytoplasmic arcades-the anastomosis between two primary processes from the same podocyte. 5,12 Similar to primary processes, the cytoplasmic arcades also contained RLPs and foot processes (Supplemental Figures 3 and 4).…”
mentioning
confidence: 96%
“…To reveal the precise architecture of podocytes, we previously examined intact podocytes reconstructed from serial sectional images of the glomerulus acquired using focused-ion beam/scanning electron microscopy (FIB/SEM) tomography (see the details of this technique in Supplemental Figure 1). [5][6][7] The reconstructed podocytes revealed that a more accurate structural hierarchy of subcellular compartments includes the "ridge-like prominence" (RLP), which protrudes directly from the basal surface of the cell body and primary process (Supplemental Figure 2). This subcellular compartment has been already recognized using conventional SEM and transmission electron microscopy and is referred to as the "central foot process" or "anchoring (foot) process. "…”
mentioning
confidence: 99%